THE INFLUENCE OF GOVERNMENT ROLES, SOCIAL RESPONSIBILITY, SOCIAL CAPITAL, AND FINANCIAL LITERACY ON WASTE BANK PERFORMANCE IN YOGYAKARTA - Nugraeni Nugraeni; Rochmad Bayu Utomo; Ni Luh Gde Ana Pertiwi (Universitas Mercu Buana Yogyakarta, 2026)
The Special Region of Yogyakarta Province is not immune to the problem of waste accumulation, which is exacerbated by the closure of the Piyungan Integrated Waste Disposal Site (TPST). This study aims to examine 1) the role of government, CSR, social Capital, and financial Literacy on social entrepreneurship orientation, 2) the role of government, CSR, social Capital, financial Literacy, and social entrepreneurship orientation on waste bank performance, 3) Social entrepreneurship orientation mediates the relationship between the role of government, CSR, social Capital, and financial Literacy on waste bank performance. The research method used is quantitative. The data source is a primary dataset collected through the distribution of questionnaires to a sample of 95 respondents. The data analysis technique used is the Structural Equation Model (SEM). The results of the study show that 1) the role of government, CSR, and financial Literacy has a positive effect on social entrepreneurship orientation. In contrast, social Capital does not affect social entrepreneurship. 2) The role of government, CSR, social Capital, financial Literacy, and social entrepreneurship orientation has a positive effect on waste bank performance. 3) Social entrepreneurship orientation mediates the role of government, CSR, social Capital, and financial Literacy on the performance of waste banks.